Effect of Professional Fighters' Weight Class on Regional Brain Volume, Cognition, and Other Neuropsychiatric Outcomes. (4th January 2022) - Char Bray, Michael Johnathan; Tsai, Jerry; Bryant, Barry; Narapareddy, Bharat; Richey, Lisa N.; Krieg, Akshay D.; Shan, Guogen; Bernick, Charles; Peters, Matthew
Abstract : Objective: To evaluate the relationship between professional fighter weight class and neuropsychiatric outcomes. Background: Traumatic brain injury (TBI) is a common source of functional impairment among athletes, military personnel, and the general population. Professional fighters in both boxing and mixed martial arts (MMA) are at particular risk for repetitive TBI and may provide valuable insight into both the pathophysiology of TBI and its consequences. Currently, effects of fighter weight class on brain volumetrics (regional and total) and functional outcomes are unknown. Design/Methods: n = 53 boxers and n = 103 MMA fighters participating in the Professional Fighters Brain Health Study (PRBHS) underwent volumetric magnetic resonance imaging (MRI) and neuropsychological testing. Fighters were divided into lightweight (=139.9 lb), middleweight (140.0–178.5 lb), and heavyweight (>178.5 lb). Results: Compared with lightweight fighters, heavyweights displayed greater yearly reductions in regional brain volume (boxers: bilateral thalami; MMA: left thalamus, right putamen) and functional performance (boxers: processing speed, simple and choice reaction; MMA: Trails A and B tests). Lightweights suffered greater reductions in regional brain volume on a per-fight basis (boxers: left thalamus; MMA: right putamen). Heavyweight fighters bore greater yearly burden of regional brain volume and functional decrements, possibly related to differing fight dynamics and force of strikes in this division. Lightweights demonstrated greater volumetric decrements on a per-fight basis. Conclusions: Although more research is needed, greater per-fight decrements in lightweights may be related to practices of weight-cutting, which may increase vulnerability to neurodegeneration post-TBI. Observed decrements associated with weight class may result in progressive impairments in fighter performance, suggesting interventions mitigating the burden of TBI in professional fighters may both improve brain health and increase professional longevity.